River Mapping using the Shallow-water Equations on GPU Clusters: Costa Rica as a Case Study - Johansell Villalobos; Daniel Caviedes-Voullième; Esteban Meneses (Revista Colombiana de Computación)
Costa Rica’s River systems play a pivotal role in providing valuable resources for society. Given that the country is exposed to a water dense, tropical climate, it is crucial to assess flooding risk and plan for extreme events. In this paper, the first step towards a river simulation pipeline is established using the Reventazón River as case study. To achieve this, an HPC portable shallow water equation solver was implemented. Boundary and initial conditions were set using QGIS and Python, and a simple Manning model was considered for friction. No rainfall, infiltration, or subsurface modeling was implemented in this work. The simulation yielded good results qualitatively on water flow for the whole Reventazón River. More complex simulations are enabled with these results given that an initial condition for water flow in the river was established.